Sugar-Sweetened Beverage but Not Diet Soda Consumption Is Positively Associated with Progression of Insulin Resistance and Prediabetes. Issue 12 (9th November 2016) - Ma, Jiantao; Jacques, Paul F; Meigs, James B; Fox, Caroline S; Rogers, Gail T; Smith, Caren E; Hruby, Adela; Saltzman, Edward; McKeown, Nicola M
Abstract: Background: Previous studies have shown an inconsistent relation between habitual beverage consumption and insulin resistance and prediabetes. Objective: The objective of the present study was to test the hypothesis that the consumption of sugar-sweetened beverages (SSBs), rather than diet soda, is associated with long-term progression of insulin resistance and the development of prediabetes. Methods: We analyzed the prospective association between cumulative mean consumption of SSBs or diet soda and incident prediabetes ( n = 1685) identified across a median of 14 y of follow-up in participants [mean ± SD age: 51.9 ± 9.2 y; 59.6% women; mean ± SD body mass index (BMI; kg/m 2 ): 26.3 ± 4.4] of the Framingham Offspring cohort. The prospective association between beverage consumption and change in homeostasis model assessment of insulin resistance (HOMA-IR; n = 2076) over ∼7 y was also analyzed. The cumulative mean consumption of SSBs and diet soda was estimated by using food-frequency questionnaires. Multivariable Cox proportional hazards models and linear regression models were implemented to estimate the HRs of incident prediabetes and change in HOMA-IR, respectively. Results: After adjustment for multiple potential confounders, including baseline BMI, we observed that SSB intake was positively associated with incident prediabetes ( P -trend < 0.001); the highest SSB consumers (>3 servings/wk; median: 6 servings/wk) had a 46% higher risk of developing prediabetes than did the SSB nonconsumers (HR: 1.46; 95% CI: 1.16, 1.83). Higher SSB intake was also associated with a greater increase in HOMA-IR ( P -trend = 0.006). No prospective associations were observed between diet soda intake and risk of prediabetes ( P -trend = 0.24) or changes in HOMA-IR ( P -trend = 0.25). These associations were similar after additional adjustment for change in BMI. Conclusion: Regular SSB intake, but not diet soda intake, is associated with a greater increase in insulin resistance and a higher risk of developing prediabetes in a group of middle-aged adults.